RELEVANSI NILAI RITUS ARUH BAGI PENGHAYATAN UPACARA SYUKUR DALAM GEREJA KATOLIK DI PAROKI AVE MARIA TANJUNG - Rumiyati.Y; Timotius Tote Jelahu; Fransiskus Janu Hamu; Titi Christiana (Sepakat : Jurnal Pastoral Kateketik, 2019)
This research was conducted to find out the understanding of the Meratus Dayak Catholics in the Parish of Ave Maria Tanjung on the Relevance of the Rite of Aruh for the Eucharistic Ceremony in the Catholic Church at Ave Maria Tanjung Parish. Through this study, it is hoped that Meratus Dayak people preserve the local culture that has been handed down and purify it based on Catholic Church teachings and deepen their faith with cultural adjustment in the thanksgiving of the Catholic Church. The method used in this research is qualitative method using phenomenology approach. Data obtained by interview, observation and documentation. The research steps include, conversation with informant, informant profile, theme determination, implication, synthesis, prospect or possibility that will happen.